Administering Public Participation. Issue 2 (February 2020) - Eckerd, Adam; Heidelberg, Roy L.
Participation and administration have long had an uneasy coexistence. On one hand, public participation in decisions that affect citizens is consistent with citizenship and democracy; on the other hand, much of what government does is complex and requires some level of technical understanding to make decisions. In this article, we report on public administrators' perceptions of public participation and the ways that they understand the participation process. We find that public participation is managed by public administrators; they determine the extent of participation, shape the ways that the participation takes place, and decide whether or not participation is valuable for their work. In some cases, the process is rather democratic, whereas in others, it is not. We find that it is up to administrators to shape the spaces for participation and select the participants in a manner consistent with their understanding of the task to be accomplished. We explore this process in the context of Environmental Impact Analysis under the National Environmental Policy Act.